2014
DOI: 10.1016/j.biortech.2014.02.108
|View full text |Cite
|
Sign up to set email alerts
|

Study on interaction between phosphorus and cadmium in sewage sludge during hydrothermal treatment by adding hydroxyapatite

Abstract: This study focused on the behavior of phosphorus (P) and its effect on cadmium (Cd) immobilization in sludge during hydrothermal treatment (HTT). The results showed that, after HTT other forms of P in sludge were almost completely converted into apatite P (AP) and the eco-toxicity and leachability of Cd was sharply decreased, signaling the immobilization effect of HTT on Cd in the sludge. Hydroxyapatite (HAP) addition showed a synergetic effect with HTT on Cd risk reduction, implying the immobilization effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Similarly, Shi et al [ 85 ] reported that ADSS has phosphorus mainly in the form of inorganic P (mainly in the form of apatite, Ca 5 (PO 4 ) 3 ), while its organic P was very low. Further, they also reported the presence of Ca (14.84%), followed by Fe (5.34%), Al (0.73%) and Mn (0.04%) in ADSS.…”
Section: Hydrothermal Carbonization Process Water Characterizationmentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, Shi et al [ 85 ] reported that ADSS has phosphorus mainly in the form of inorganic P (mainly in the form of apatite, Ca 5 (PO 4 ) 3 ), while its organic P was very low. Further, they also reported the presence of Ca (14.84%), followed by Fe (5.34%), Al (0.73%) and Mn (0.04%) in ADSS.…”
Section: Hydrothermal Carbonization Process Water Characterizationmentioning
confidence: 95%
“…HTC substantially stabilizes phosphorus (P) during the processes [ 88 ], as P is mainly immobilized and retained within the hydrochar. Shi et al [ 85 ] reported the redistribution of P and the major metals closely related to the existing forms of P in process waters and hydrochar after HTC of ADSS. Very small amounts of P, Ca, Al, Fe and Mn were detected to be released into process waters (<0.6%) while the majority of them were accumulated in the hydrochar, and the extent of this kind of accumulation increased with the increase of treatment temperature.…”
Section: Hydrothermal Carbonization Process Water Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon addition of CaO, increased OHconcentration facilitated dissolution of AlPO4 to release PO 3-4 which subsequently reacted with Ca 2+ to precipitate as Ca3(PO4)2 (Shi et al, 2014;Yildiz Bircan et al, 2011). Moreover, it was deduced that dissolved PO 3-4 may react with CaF2 to form Ca5(PO4)3F (Wang et al, 2013).…”
Section: Mineralization Behavior Of Heteroatomic Compoundsmentioning
confidence: 99%
“…In addition, transformation behaviors and environmental risk of heavy metals in solids have been extensively discussed for land application (Leng et al, 2014;Shi et al, 2013;Zhai et al, 2014). Moreover, simultaneous extraction, decomposition, and stabilization processes during HTC could result in mineralization and migration of inorganic elements in SS (Shi et al, 2014). Although heavy metals tended to be accumulated and redistributed in solid residues after sub-and supercritical water (SCW) treatment (Shi et al, 2013;Zhai et al, 2014), the distribution of heavy metals in liquid phase is also of great importance for post-treatment and reclamation of the processing effluents.…”
Section: Introductionmentioning
confidence: 99%